Iron‐Based Nanocatalysts for Electrochemical Nitrate Reduction. Issue 10 (14th September 2022) - Wang, Chuqi; Zhang, Yingbing; Luo, Hongxia; Zhang, Hui; Li, Wei; Zhang, Wei‐xian; Yang, Jianping
Abstract: Nitrate has a high level of stability and persistence in water, endangering human health and aquatic ecosystems. Due to its high reliability and efficiency, the electrochemical nitrate reduction reaction (NO3 RR) is regarded as the best available option for mitigating excess nitrate in water and wastewater, especially for the removal of trace levels of nitrate. One of the most critical factors in the electrochemical reduction are the catalysts, which directly affect the reaction efficiency of nitrate removal. Iron‐based nanocatalysts, which have the advantages of nontoxicity, wide availability, and low cost, have emerged as a promising electrochemical NO3 RR material in recent years. This review covers major aspects of iron‐based nanocatalysts for electrochemical NO3 RR, including synthetic methods, structural design, performance enhancement, electrocatalytic nitrate reduction test, and reduction mechanism. The recent progress of iron‐based nanocatalysts for electrochemical NO3 RR and the mechanism of functional advantages for modified structures are reviewed from the perspectives of loading, doping, and assembly strategies, in order to realize the conversion from pollutant nitrate to harmless nitrogen or ammonia and other sustainable products. Finally, challenges and future directions for the development of low‐cost and highly‐efficient iron‐based nanocatalysts are explored. Abstract : This review summarizes recent progress in iron‐based nanocatalysts for electrochemical nitrate reduction, and figures out the relationship between the structure and electrocatalytic performance in detail. These summaries add to the understanding of structure engineering for iron nanoparticles and provide a systematic theoretical foundation for developing low‐cost, high‐performance iron‐based electrocatalysts.